Genomic instability in cultured stem cells: associated risks and underlying mechanisms. (September 2011) - Ross, Andrew L; Leder, Daniel E; Weiss, Jonathan; Izakovic, Jan; Grichnik, James M
Embryonic stem cells, mesenchymal stem cells and induced pluripotent stem cells expanded in vitro exhibit genomic instability. Commonly reported abnormalities include aneuploidy, deletions and duplications (including regions also amplified in cancer). Genomic instability confers an increased risk of malignant transformation that may impact the safety of cultured stem cell transplantation. Possible mechanisms responsible for this genomic instability include DNA repair mechanism abnormalities, telomere crisis, mitotic spindle abnormalities and inappropriate induction of meiotic pathways. Prior to widespread use of these cells in regenerative medicine, it will be critical to gain an understanding of the mechanisms responsible for genomic instability to develop strategies to prevent the accrual of chromosomal defects during expansion in vitro .